Conflict Management And How To Manage Conflict In Organizations - Andres Dharma Nurhalim (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
Conflicts that occur in an organization can hinder achieving the desired goals, therefore conflicts need to be managed properly so that their impact can be minimized. This study aims to describe conflict within an organization, what factors cause conflict, approaches to conflict resolution, and the impact of conflict on organizational performance. The type of research used is a literature study. From the results of the research that the author did, namely (1) conflict can be interpreted with 3 meanings namely positive, neutral, and negative meanings, (2) the factors that cause conflict can come from external and internal factors of individual organizations. Internal factors can be personality differences, stress, decreased productivity and so on. While external factors can be in the form of communication problems, limited resources, sexual harassment, and so on, (3) the approach to dealing with conflict requires leadership skills. There are eight conflict handling approaches namely, deliberation, third party intervention, confrontation, bargaining (bargaining), compromise, mediation, conciliation and consultation, and increasing resources, and (4) an individual's performance can be hampered due to conflict, but Not all conflicts have a negative impact, conflict can have a positive impact if it can be managed properl